Product innovation and cause-related marketing success: A conceptual framework and a research agenda - Christofi, Michael; Vrontis, Demetris; Leonidou, Erasmia (My University, 2014)
Purpose: The purpose of this paper is twofold. First, the authors aim to identify all the product- and brand-related factors that promote cause-related marketing (CRM) success. The second part of this research aim is, to undertake a product innovation theory application into the context of CRM, examine the degree and nature of its theoretical and practical consonance, and develop an integrated conceptual framework for CRM success. Design/methodology/approach: The paper is conceptual and incorporates and interrelates the findings of existing CRM research as applied within the context of corporate social responsibility (CSR). Specifically this paper accumulates the state of prior wisdom on CRM success through the identification of several product- and brand-related success factors, based on a systematic review of the literature. In doing so, it introduces the concept of product innovation as a CRM success factor and integrates those distinct fields into a conceptual framework. Findings: The authors develop an integrative framework and a propositional inventory that represents a consolidated foundation for the systematic development of a theory for successful CRM strategies, along with the integration of product innovation within the field of CRM. Research limitations/implications: Towards this direction, the objective of this study is theory construction rather than theory testing. Thus, much work remains to be done in terms of empirically testing our research propositions. In conclusion, this paper posits a set of research directions designed to enable scholars to further advance the integration of product innovation and CRM from both problem-driven theory development as well as theory-driven practice management perspectives. Originality/value: The value of this paper accumulates the state of prior wisdom on CRM success, a notion with increasing use by corporations in recent years. Furthermore, this paper appears to be the first of its kind to examine, from the theorist perspective, the dynamics implied by synthesizing these, so far, distinct concepts. Additionally, the research adds appreciable value to academic knowledge on the fundamental discussion of the bidirectional relationship between CSR and innovation, also contributing an analogous CRM success framework to the existing wisdom. © Emerald Group Publishing Limited.
Keywords: Product innovation; Success factors; Cause-related marketing; Corporate social responsibility